Determinants and perception of health insurance participation among healthcare providers in Nigeria: A mixed-methods study. - Hezekiah Olayinka Shobiye (Public Library of Science (PLoS), 2021)
Background To accelerate universal health coverage, Nigeria's National Health Insurance Scheme (NHIS) decentralized the implementation of government health insurance to the individual states in 2014. Lagos is one of the states that passed a State Health Insurance Scheme into law, in order to expand the benefits of health insurance beyond the few residents enrolled in community-based health insurance programs, commercial private health insurance plans or the NHIS. Public and private healthcare providers are a critical component of the Lagos State Health Scheme (LSHS) rollout. This study explored the determinants and perception of provider participation in health insurance programs including the LSHS. Methods This study used a mixed-methods cross sectional design. Quantitative data were collected from 60 healthcare facilities representatively sampled from 6 Local Government Areas in Lagos state. For the qualitative data, providers were interviewed using structured questionnaires on selected characteristics of each health facility in addition to the managers' opinions about the challenges and benefits of insurance participation, capacity pressure, resource availability and financial management consequences. Results A higher proportion of provider facilities participating in insurance relative to non-participating facilities were larger with mid to (very) high patient volume, workforce, and longer years of operation. In addition, a greater proportion of private facilities compared to public facilities participated in insurance. Furthermore, a higher proportion of secondary and tertiary facilities relative to primary facilities participated in insurance. Lastly, increase in patient volume and revenue were motivating factors for provider facilities to participate in insurance, while low tariffs, delay and denial of payments, and patients' unrealistic expectations were mentioned as inhibiting factors. Conclusion For the Lagos state and other government insurance schemes in developing countries to be successful, effective contracting and quality assurance of healthcare providers are essential. The health facilities indicated that these would require adequate and regular provider payment, investments in infrastructure upgrades and educating the public about insurance benefit plans and service expectations.